Effect of Hepatic Impairment on Cobimetinib Pharmacokinetics: The Complex Interplay Between Physiological Changes and Drug Characteristics. Issue 2 (21st July 2020) - Cheeti, Sravanthi; Deng, Yuzhong; Chang, Ilsung; Georgescu, Isabela; Templeton, Ian; Choong, Nicholas; Cheung, Kit Wun Kathy; Girish, Sandhya; Musib, Luna
Abstract: Cobimetinib is a kinase inhibitor indicated for use in combination with vemurafenib for treatment of unresectable/metastatic melanoma with specific BRAF mutations. Cobimetinib is extensively metabolized in liver; thus, patients with hepatic impairment (HI) might have increased cobimetinib exposure. In this study, we investigated the impact of HI on the pharmacokinetics (PK) and safety of cobimetinib. Subjects with normal hepatic function and mild to severe HI were enrolled. All subjects received a single oral dose of 10 mg cobimetinib, and serial blood samples were collected at specified times. Cobimetinib PK in subjects with mild and moderate HI was similar to that in those with normal liver function. However, subjects with severe HI, on average, showed ∼30% lower total AUC0‐∞ and ∼2‐fold higher unbound AUC0‐∞ compared with those with normal hepatic function. These exposure differences can be explained by lower albumin levels observed in subjects with severe HI, the strong correlation between albumin level and the unbound fraction and the general PK variability of cobimetinib. In addition, previous studies with cobimetinib showed a lack of an exposure‐response relationship for efficacy and safety. Therefore, collectively, our results suggest that the starting dose for patients with hepatic impairment can be the same as that for those with normal hepatic function.